2023
DOI: 10.3390/app13042062
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cyberbullying Patterns in Low Resource Colloquial Roman Urdu Microtext using Natural Language Processing, Machine Learning, and Ensemble Techniques

Abstract: Social media platforms have become a substratum for people to enunciate their opinions and ideas across the globe. Due to anonymity preservation and freedom of expression, it is possible to humiliate individuals and groups, disregarding social etiquette online, inevitably proliferating and diversifying the incidents of cyberbullying and cyber hate speech. This intimidating problem has recently sought the attention of researchers and scholars worldwide. Still, the current practices to sift the online content an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Hint: 1 (Agrawal & Awekar, 2018;A. Ali & Syed, 2020;Dewani et al, 2023;Raj et al, 2021;Zubair et al, 2023). Table 4 shows that this research enhances accuracy, precision, memory, and F1-score evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Hint: 1 (Agrawal & Awekar, 2018;A. Ali & Syed, 2020;Dewani et al, 2023;Raj et al, 2021;Zubair et al, 2023). Table 4 shows that this research enhances accuracy, precision, memory, and F1-score evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…In their experiment, they tested the approaches with 30% of the dataset and showed a hybrid approach with lexicon features achieved superior performance, and models with SVM as classifier also achieved better performance amongst the ML algorithms deployed. Dewani et al [37] showed that SVM and embedded hybrid N-gram approach performed best in detecting cyberbullying in the Roman Urdu language context, with an accuracy of 83%. Suhas-Bharadwaj et al [38] applied extreme learning machine to classify cyberbullying messages, and achieved accuracy of 99% and an F1 score of 91%.…”
Section: Related Workmentioning
confidence: 99%